Human side of lean manufacturing at Technicolor - Bollinger, Steven R.; Society of Manufacturing Engineers ([Michigan] : Society of Manufacturing Engineers, 2004)
This video show how the VHS duplicator Technicolor company was able to tap into the power of employee ideas to help their business thrive by building employee trust
Code no : DV04PUB15
Title from title screen
Graphics by Jerome T. Cook ; editor, Jim O'Donnel
Keywords: Manufacturing processes; Production planning; Process control